FAKTOR-FAKTOR DETERMINAN PROSES DAN HASIL BELAJAR SISWA SMU - M. Asrori (Universitas Negeri Yogyakarta, 2002)
Abstract The purpose of this research is to find the determinant factors of the learning process and achievement of Upper Secondary School Students’ at West Kalimantan. 1200 students and 120 teachers was involved as participant or research subject. There are five variables (students learning habit, teaching profession commitment, school system management, evaluation system, and teachers’ cognitive capacity) as exogenous variables; whereas teaching performance as endogenous variable; and students’ achievement as dependent variable. Questionnaire, test and inventory were administered in order to find all the data. Descriptive analysis indicates that the school management tends to be at high score and the other variables are moderate and lower level. Path analysis indicates that teachers’ cognitive capacity and the students learning habit were affect directly to the students; cognitive capacity (students’ achievement). Furthermore, teaching profession commitment influences to the teaching performance but not affect directly to the students’ achievement. On the other hand, the reminder variables have no influence whether or not directly to the students’ achievement. Keywords: determinant factors, teaching-learning process, and students’ achievement